The Use of Taguchi Method in Design of Dies Propeller Production Using CNC Machine - Jadmiko, Edi; Wahyunugroho, Purwadi (International Journal of Marine Engineering Innovation and Research, 2020)
Propeller is a rounded blade that rotates in a circle, helping to move a vehicle by pushing against water or air. A speed boat's propeller moves it forward by spinning against the water. Propellers use the laws of physics to propel, or drive forward, an aircraft or a boat. The basic structure of a propeller is a spinning or rotating the shaft with wide, curved blades attached to it. The very simplest propellers were first used in ancient Greece, where the inventor Archimedes invented a "screw propeller" that moved water for irrigating crops. A method for making propeller is to use a casting method with sand mold. In operating the sand mold can only be used for one use, and in the molding process must be reconstructed which of course requires cost and additional time so it is less efficient. Therefore, making a propeller with a permanent mold is the right solution. In this study, the design of dies propeller production process with CNC (Computerized Numerical Control) machine was designed using the MasterCam software simulation method. In addition, variations in machining parameters feed rate, retract rate and depth of cut were also carried out using the Taguchi method. From the research has known the step of dies propeller production process and the time for cutting that used to calculate the most efficient variable variation. Based on the simulation that has been done, for making dies propellerÂ  requires ten steps of processing, there are facing, pocket, contour (top die), surface rough pocket, surface finish contour (top die), surface finish parallel, contour (bottom die), and surface finish contour (bottom die). From a series of work processes designed, the total processing time was produced for top die 729,17 minutes and cutting power was 9,734 kWh and for bottom die is about 1329,65 minutes and cutting power was 14,543 kWh.